EVALUASI KEBIJAKAN RUMAH TUNGGU KELAHIRAN (RTK) DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA TAHUN 2016 - Sri Ayu Lestari; Laksono Trisnantoro; Dwi Handono Sulistyo (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2019)
Background: The high maternal mortality rate (MMR) in Indonesia prompted the government to issue a Jampersal fund policy. One of the objectives of Jampersal fund is to provide budget for operational activities of Maternity Waiting Home (MWH) Program, a government strategy to facilitate access of pregnant mother to get health service to overcome pregnant, childbirth and childbirth problems as an effort to decrease maternal MMR in Indonesia. Objective: To describe the implementation of MWH policy as an effort to facilitate pregnant women, childbirth, and postpartum to get access to health service in Konawe Regency of Southeast Sulawesi Province. Methods: The study was descriptive using qualitative design with case study approach focusing on developing in-depth description and analysis of cases also studying MWH program. Results: MWH Program in Konawe Regency has been running for one year but there was still one Puskesmas that has not run the MWH program because the location of Puskesmas is far from the citizen’s residence. MWH is not only used by pregnant women who are far from the health facility and have a high risk but also used for all pregnant women who will give birth. MWH already meets the criteria set by the Ministry of Health. The operational cost of the waiting house guarantees all the costs of pregnant and family needs during their stay. The obstacles to MWH programs were disbursement of funds, rejection of pregnant women to the waiting house and difficult road access. Conclusion: MWH Program has been effective because it has been used by all pregnant women who have risk and who will give birth are placed in the waiting house of birth. The barriers that exist during the MWH program runs were disbursement of funds, the rejection of pregnant women into waiting homes and difficult road access.